Stabilisation of aeolian sand with geopolymer and fines for use as pavement foundation - Rui Chen; Hai Chen; Xiaoding Ke; Ruoyu Hao; Yixian Wang (European Journal of Environmental and Civil Engineering, 2026)

Effects of evidence-based perineal massage on maternal and neonatal physiological outcomes and childbirth experience in primiparous women: A quasi-experimental study - Yuxuan Li; Linlin Cao; Hongxiao He; Haishan Wei; Hong Lu; Shenglian Ni; Jie Lu; Ruiqing Dong; Mengting Wang; Xiaoding Zhou (Next Research, 2026)

Mechanistic insights into the long-term stabilization of Cr(VI) by modified nanoscale zero-valent iron in sediments - Yiqun Xu; Jie Dai; Leixin Huang; Weilong Lin; Yunlong Zhu; Xiaoding Huang; Rongzhong Wang; Binbin Shao; Wenjing Xue (Journal of Contaminant Hydrology, 2026)

Enhanced activation of peracetic acid by Cu2O under sunlight through coordination environment regulation: Improved charge separation and peracetic acid adsorption/complexation via uncoordinated Cu atoms - Jinpeng Wang; Yuqing Cao; Yi Han; Xiaoding Huang; Xiaoyong Wu; Hefa Cheng; Dejin Wang (Chemical Engineering Journal, 2026)

Retraction notice to “Influence of low voltage electric field stimulation on hydrogen generation from anaerobic digestion of waste activated sludge” [Sci. Total Environ. 704 (2020) 135849] - Ziletao Tao; Dongbo Wang; Fubing Yao; Xiaoding Huang; You Wu; Yanxin Wu; Zhuo Chen; Jing Wei; Xiaoming Li; Qi Yang (Science of The Total Environment, 2026)

Study on Long-Term Deformation Prediction and Creep-Damage Model of Rock - Yipin Liu; Tingting Ma; Shuguang Zhang; Xiaoding Wang; Xiaodong Sun; Wenbo Liu (Pure and Applied Geophysics, 2026)

Green Revolution-associated DELLA accumulation enhances salt tolerance in cereals by disrupting INDETERMINATE SPIKELET1 biomolecular condensates - Xiliu Cheng; Haoran Wang; Mingjie Lyu; Meiting Gao; Guogen Zhang; Yanjia Gong; Yanqing Chen; Xianjun Sun; Xiaoding Ma; Weihua Qiao; Fan Zhang; Jun Liu; et al. (Molecular Plant, 2026)

Intelligent Diagnosis of Ship Propulsion Motor Bearings Based on Dynamic Class Weights - Guohua Yan; Xiaoding Wang; Kai Liu; Jingran Kang; Xinhua Yi (Journal of Marine Science and Engineering, 2025)
As an important part of the ship’s power system, the bearing operation status of the propulsion motor is directly related to the reliability and safety of the whole system. However, in the field of marine propulsion motor bearing fault diagnosis, the data imbalance problem seriously affects the performance of the fault detection model. Due to the scarcity of fault data relative to normal operation data, traditional diagnostic methods are ineffective in dealing with unbalanced data. To solve this problem, a dynamic class weighting solution is proposed. The dynamic class weighting method introduces the weight coefficient λ on the basis of the traditional class weighting, which can adjust the class weight value in real time according to the training situation, and comprehensively considers the data distribution and the training situation to ensure that the model can learn better even in the case of insufficient data. Testing on the imbalanced distribution of bearing natural-failure data shows that the proposed method achieves a 5.25% improvement in diagnostic accuracy compared to direct training. Compared with traditional class-weighted approaches, diagnostic accuracy is enhanced by 3.56%, effectively mitigating the impact of scarce and unevenly distributed failure data on model training.

Towards the digitalization of water treatment facilities: A case study on machine learning-enabled digital twins - Zeyu Ma; Yunyi Zhu; Chunsheng Chen; Ting Li; Yanan Li; Xiaoding Li; Yuan Wang; T. David Waite; Jing Guan (Journal of Water Process Engineering, 2025)

Protocol for the purification and culture of primary retinal ganglion cells and development of common pathological models - Xiaoding Shui; Yan Wang; Yu Luo; Xiaoyu Liang; Tao Chen; Yanting Xia; Qiping Wei; Liang Liao (Journal of Molecular Histology, 2025)

Advances in Supercell Storm Research - Xiuming Wang; Huan Tang; Xiaoding Yu; Yuhao Zheng; Chenxi Wang; Haiyan Fei (Journal of Meteorological Research, 2025)

Large-scale genomic and phenomic analyses of modern cultivars empower future rice breeding design - Xiaoding Ma; Hao Wang; Shen Yan; Chuanqing Zhou; Kunneng Zhou; Qiang Zhang; Maomao Li; Yaolong Yang; Danting Li; Peng Song; Cuifeng Tang; Leiyue Geng; et al. (Molecular Plant, 2025)

Correction to: An Innovative Mechanism of Directional Rock Cracking Mechanics and Mine Pressure Control Method for Energy-Gathering Blasting - Xiaoding Xu; Yuejin Zhou; Jun Yang; Yubing Gao; Chun Zhu; Yajun Wang; Qiang Fu (Rock Mechanics and Rock Engineering, 2024)

Digital evolution and twin miracle of sugarcane breeding - Xiaoding Wang; Qibin Wu; Haitao Zeng; Xu Yang; Xuechao Yang; Xun Yi; Ibrahim Khalil; Youxiong Que (Field Crops Research, 2024)

An Innovative Mechanism of Directional Rock Cracking Mechanics and Mine Pressure Control Method for Energy-Gathering Blasting - Xiaoding Xu; Yuejin Zhou; Jun Yang; Yubing Gao; Chun Zhu; Yajun Wang; Qiang Fu (Rock Mechanics and Rock Engineering, 2024)

The resistance of hydrogenotrophic methanogenic microorganisms to ofloxacin in sludge anaerobic digestion process - Yanxin Wu; Chao Wu; Xuran Liu; Hongbo Chen; Zhiyi Deng; Dongbo Wang; Zhixing Wu; Shenglan Tang; Xiaoding Huang (Journal of Environmental Management, 2024)

Thermal treatment of municipal solid waste incineration fly ash and nanofiltration membrane concentrate co-processing: Speciation of chromium and its leachability - Qian Wu; Zongru Wu; Hao Wu; Qingxu Wang; Nannan Huang; Jieya Zhou; Xiaoding Li; Lihu Shi; Shulei Tian; Meitong Li (Journal of Cleaner Production, 2023)

Performance and mechanisms of citric acid improving biotransformation of waste activated sludge into short-chain fatty acids - Xiaodong Zhang; Xiaoding Huang; Xiaoming Li; Jiamin Zhang; Mengge Tang; Xuran Liu; Dongbo Wang; Qi Yang; Abing Duan; Junwu Liu (Bioresource Technology, 2023)

Synoptic-Scale Analysis on Development and Maintenance of the 19–21 July 2021 Extreme Heavy Rainfall in Henan, Central China - Dorina Chyi; Xiuming Wang; Xiaoding Yu; Junhui Zhang (Journal of Meteorological Research, 2023)

Genomic footprints of Kam Sweet Rice domestication indicate possible migration routes of the Dong people in China and provide resources for future rice breeding - Chunhui Liu; Tianyi Wang; Huicha Chen; Xiaoding Ma; Chengzhi Jiao; Di Cui; Bing Han; Xiaobing Li; Aixia Jiao; Renchao Ruan; Dayuan Xue; Yanjie Wang; et al. (Molecular Plant, 2023)

Investigation of Instability and Blasting Caving Technology of Composite Support Structure in the Goaf of Gypsum Mine - Pang Shun; Xiaoding Xu; Yuejin Zhou; Guchun Zang; Jun Wang (Geotechnical and Geological Engineering, 2021)

Development of recycled polylactic acid/oyster shell/biomass waste composite for green packaging materials with pure natural glue and nano-fluid - Dingtian Xiao; Shan Qing; Pengfei Chen; Zhifeng Yu; Huaqiang Xiao; XiaoDing Wang (Environmental Science and Pollution Research, 2020)

DNA Mismatch Repair Deficiency Detection in Colorectal Cancer by a New Microsatellite Instability Analysis System - Shafei Wu; Xiaoding Liu; Jing Wang; Weixun Zhou; Mei Guan; Yuanyuan Liu; Junyi Pang; Tao Lu; Liangrui Zhou; Xiaohua Shi; Huanwen Wu; Zhiyong Liang; et al. (Interdisciplinary Sciences: Computational Life Sciences, 2020)
Background Although microsatellite instability (MSI) is most commonly detected in colorectal cancer (CRC), improvement in MSI analysis method can always help us better assessing MSI phenotypes and gaining useful information in challenging cases. The purpose of current study is to explore whether the ProDx® MSI analysis System (ProDx® MSI) can improve MSI classification in CRC. Methods We compared the MSI profiles of 97 FFPE samples from CRC patients by ProDx® MSI with Promega MSI analysis System 1.2 and NCI panel. The result is then confirmed by IHC test, which evaluate MMR protein expression. Furthermore, next generation sequencing was performed to double confirm the specimens with discordant results. Results Among the total 97 CRC cases, 35 were scored as MSI-High by ProDx® MSI, Promega MSI analysis System 1.2, and NCI panel simultaneously. Three extra MSI-High cases were identified by ProDx® MSI. These three cases were classified as MSI-Low by NCI panel, while two of these as MSI-Low, and 1 as MSS by Promega MSI analysis System 1.2. ProDx® MSI had higher concordance with IHC detection compared with Promega MSI Analysis System 1.2 and NCI panel at 99.0%, 96.9%, and 95.9%, respectively. The ProDx® MSI distinguished MSI status with 100% sensitivity and 98.4% specificity. Our data showed that MSI-High phenotype occurred most frequently in tumor development stage I and stage II. Conclusions The colorectal cancer can be classified according to MSI status accurately by ProDx® MSI. More cases with MSI-High feature may be revealed by ProDx® MSI than by previous test systems in colorectal cancer.

Sulfate radical-mediated degradation of phenol and methylene blue by manganese oxide octahedral molecular sieve (OMS-2) activation of peroxymonosulfate - Jing Wei; Xiaoming Li; Qi Yang; You Wu; Xiaoding Huang; Ziletao Tao; Qiuxiang Xu; Xiaofei Zhu; Dongbo Wang (Environmental Science and Pollution Research, 2019)

Identification of quantitative trait loci associated with drought tolerance traits in rice (Oryza sativa L.) under PEG and field drought stress - Bing Han; Jiao Wang; Yafei Li; Xiaoding Ma; Sumin Jo; Di Cui; Yanjie Wang; Dongsoo Park; Youchun Song; Guilan Cao; Xingsheng Wang; Jianchang Sun; et al. (Euphytica, 2018)

A method to estimate the abundance of fish based on dual-frequency identification sonar (DIDSON) imaging - Danxiang Jing; Jun Han; Xiaoding Wang; Guanyu Wang; Jianfeng Tong; Wei Shen; Jin Zhang (Fisheries Science, 2017)

A knockdown mutation of YELLOW-GREEN LEAF2 blocks chlorophyll biosynthesis in rice - Hong Chen; Zhijun Cheng; Xiaoding Ma; Han Wu; Yanling Liu; Kunneng Zhou; Yilin Chen; Weiwei Ma; Jingcui Bi; Xin Zhang; Xiuping Guo; Jiulin Wang; et al. (Plant Cell Reports, 2013)

BEAK LIKE SPIKELET1 is Required for Lateral Development of Lemma and Palea in Rice - Xiaoding Ma; Zhijun Cheng; Fuqing Wu; Mingna Jin; Liguo Zhang; Feng Zhou; Jiulin Wang; Kunneng Zhou; Jian Ma; Qibing Lin; Cailin Lei; Jianmin Wan (Plant Molecular Biology Reporter, 2013)